Plagiarism and Authorship Credit - Albina Arjuman; Somen N. Chakraborty (Indian Journal of Public Health, 2024)
Literature being an expression of an author, its commodification historically has assigned a value to it primarily in terms of authorship credit. Arguably reproducing published content without attributing the requisite source, termed as plagiarism is ethically discrediting to this premise. However, simply weighing its proportion based on digitally assigned semantic similarity may not be completely justifiable in the present-day digital atmosphere. It should be noted that while technology can facilitate plagiarism detection, digitization by way of providing greater access to published content is also the facilitator of plagiarism. While the scientific community is often severe in its approach toward the act of plagiarism, there is still a lack of clarity around the code of conduct of the same as there are several grey areas related to such a misconduct on which the law remains silent. By revisiting the historical evolution of the credit of authorship and the copyright law this piece presents an analytical vista pertaining to plagiarism in a different light. By identifying the gaps in the present-day handling of these age-old concepts, one may find that there is an unmet need to revisit the legal aspects of handling cases of plagiarism taking into consideration the digital environment.